Sistem Pakar Pemilihan Sampo Pria Dengan Menggunakan Metode Certainty Factor - Putra Syahwal Alam; Agus Wantoro Wantoro; Kisworo Kisworo (Universitas Teknokrat Indonesia, 2022)
Shampoo is a hair care product that is used to gradually remove oil, dirt, skin particles, dandruff and other contaminant particles that accumulate in the hair. Shampoo when given water, is a suffactant for cleansing hair and scalp, removing natural oils that lubricate the hair shaft. Shampoo comes from the Hindi word champo, which comes from the Sanskrit chapayati meaning to calm. The system development method uses the waterfall method and system design uses the UML system. This research begins with literary studies and data studies. Then this Expert System is designed and implemented using the Definitty Factor method in choosing the right male shampoo.The results achieved by having a male shampoo selection expert system will make it easier for users to choose the right shampoo based on hair type and the problems that exist in each user. Shampoo is a hair care product that is used to gradually remove oil, dirt, skin particles, dandruff and other contaminant particles that accumulate in the hair. Shampoo when given water, is a suffactant for cleansing hair and scalp, removing natural oils that lubricate the hair shaft. Shampoo comes from the Hindi word champo, which comes from the Sanskrit chapayati meaning to calm. The system development method uses the waterfall method and system design uses the UML system. This research begins with literary studies and data studies. Then this Expert System is designed and implemented using the Definitty Factor method in choosing the right male shampoo.The results achieved by having a male shampoo selection expert system will make it easier for users to choose the right shampoo based on hair type and the problems that exist in each user.